Investigation of flow and heat transfer instabilities and oscillation inhibition of n-decane at supercritical pressure in vertical pipe. (October 2019) - Zhu, Yinhai; Zhao, Ran; Wang, Yusen; Jiang, Pei-Xue
Highlights: The characteristics of flow and heat transfer instabilities of supercritical n-decane are studied. The transition oscillation and Helmholtz oscillation are observed. An increase in inlet temperature, pressure, or mass flow-rate weaken flow oscillation. A novel oscillation inhibition method by inserting of twisted wires from certain parts of tube was proposed. The insertion of twisted wire into the entire length of the tube has the greatest PEC. Abstract: The characteristics of the flow and heat transfer instabilities of n-decane at supercritical pressures were evaluated under different inlet temperature, pressure, mass flow, and flow direction conditions. The experiment was carried out in a vertical heating tube with an inner diameter of 2 mm, at a maximum heat flux density of 200 kW/m 2, under both laminar and turbulent inlet conditions. The results revealed that an increase in the inlet temperature, pressure, or mass flow rate can weaken the flow and heat transfer oscillation. Two oscillation stages of were observed, one is the transition oscillation that occurs when the fluid flows from laminar to turbulent, the other is the Helmholtz oscillation due to the uneven distribution of the radial density and the density distribution in the flow direction. Furthermore, a novel oscillation inhibition method was proposed, which involves the insertion of a twisted stainless-steel wire from certain parts of the heating tube. The influence of the insertion methods on the heat transfer enhancement and oscillation inhibition was evaluated using a comprehensive heat transfer coefficient. The results revealed that the insertion of a twisted wire from the tube inlet was more effective for the inhibition of the oscillation than that from the tube outlet. The insertion of a twisted wire into the entire length of the tube resulted in the best comprehensive performance of heat transfer and flow resistance when compared with those of other insertion methods.